2015
DOI: 10.1038/srep18169
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mycoparasitism-related genes in Clonostachys rosea 67-1 active against Sclerotinia sclerotiorum

Abstract: Clonostachys rosea is a mycoparasite that has shown great potential in controlling various plant fungal pathogens. In order to find mycoparasitism-related genes in C. rosea, the transcriptome of the efficient isolate 67-1 in association with sclerotia of Sclerotinia sclerotiorum was sequenced and analysed. The results identified 26,351 unigenes with a mean length of 1,102 nucleotides, among which 18,525 were annotated in one or more databases of NR, KEGG, Swiss-Prot, GO and COG. Differentially expressed genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…In a previous study, the endochitinase-encoding gene Chi67 - 1 was found to be significantly upregulated in C. rosea 67-1 parasitizing S. sclerotiorum , compared with expression in 67-1 not exposed to S. sclerotiorum (Sun et al 2015b). Therefore, we decided to attempt to genetically engineer a highly efficient biocontrol strain by overexpressing this gene.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a previous study, the endochitinase-encoding gene Chi67 - 1 was found to be significantly upregulated in C. rosea 67-1 parasitizing S. sclerotiorum , compared with expression in 67-1 not exposed to S. sclerotiorum (Sun et al 2015b). Therefore, we decided to attempt to genetically engineer a highly efficient biocontrol strain by overexpressing this gene.…”
Section: Discussionmentioning
confidence: 92%
“…Transcriptome sequencing and analysis of 67-1 parasitizing S. sclerotiorum sclerotia revealed a remarkable up-regulation of Chi67 - 1 , which encodes a 37 kDa endochitinase. The presence of this gene suggested that Chi67 - 1 was correlated with mycoparasitism of C. rosea (Sun et al 2015b). Therefore, in the present study, we investigated the role of this chitinase in mycoparasitism of C. rosea against S. sclerotiorum , and assessed the efficiency of 67-1 transformants overexpressing Chi67 - 1 against Sclerotinia rot of soybean, with the intention of improving the biocontrol of C. rosea .…”
Section: Introductionmentioning
confidence: 99%
“…MFS transporter genes induced during interactions with B. cinerea and F. graminearum almost exclusively belonged to these expanded MFS families, indicating that efflux-mediated protection against exogenous or endogenous secondary metabolites and nutrient uptake are important components of the mycoparasitic attack in C. rosea. MFS transporters were reported to be induced in several other mycoparasitic species, including the closely related C. chloroleuca (Moreira, Abreu, Carvalho, Schroers, & Pfenning, 2016;Sun, Sun, & Li, 2015), Trichoderma spp. (Atanasova, Le Crom et al, 2013;Seidl et al, 2009;Steindorff et al, 2014), Tolypocladium ophioglossoides (Quandt, Di, Elser, Jaiswal, & Spatafora, 2016), Escovopsis weberi (de Man et al, 2016), Pythium oligandrum (Horner, Grenville-Briggs, & Van West, 2012) and Ampelomyces quisqualis (Siozios et al, 2015), but without proper identification of family classification it is difficult to speculate about their exact biological role in these species.…”
Section: Discussionmentioning
confidence: 99%
“…reduced the colonization of Fusarium species in wheat and maize plants (Luongo et al 2005 andWoo et al 2006). When taking into account that G. roseum had biosynthetic gene clusters to encode a large number of enzyme complexes and secondary metabolites, reported by Karlsson et al (2015) and Sun et al (2015), it was suggested that the main reason of antagonistic activity was related to the production of antifungal substances such as enzymes and secondary metabolites. In this manner, as a result of the interaction among them, G. roseum might damage to the cell structure along with hyphal penetration and promote disruption of pathogen cell.…”
Section: In Vitro Antagonistic Activity Of the Bio-agentsmentioning
confidence: 99%